2019
DOI: 10.1155/2019/2901840
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Antioxidant Enzymes in the Tumor and Adjacent Noncancerous Tissues of Non-Small-Cell Lung Cancer

Abstract: Lung tissue is directly exposed to high oxygen pressure, as well as increased endogenous and exogenous oxidative stress. Reactive oxygen species (ROS) generated in these conditions play an important role in the initiation and promotion of neoplastic growth. In response to oxidative stress, the antioxidant activity increases and minimizes ROS-induced injury in experimental systems. The aim of the present study was to evaluate the activity of antioxidant enzymes, such as superoxide dismutase (SOD; isoforms: Cu/Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 48 publications
1
42
0
Order By: Relevance
“…3B). SOD and GPx are two important antioxidant enzymes (36). The enzymatic activities of SOD and GPx in the brains of MCAO model mice were found to be decreased (Fig.…”
Section: Sino Treatment Mitigates Mcao-associated Inflammation and Oxidative Stressmentioning
confidence: 95%
“…3B). SOD and GPx are two important antioxidant enzymes (36). The enzymatic activities of SOD and GPx in the brains of MCAO model mice were found to be decreased (Fig.…”
Section: Sino Treatment Mitigates Mcao-associated Inflammation and Oxidative Stressmentioning
confidence: 95%
“…Many studies confirmed our findings regarding the lower levels of SOD in lung cancer patients' pre-treatment with cisplatin. 14,4 Moreover, cisplatintreated patients showed no significant differences comparing with control. Little information is known about the correlation between cisplatin and SOD activity.…”
Section: Antioxidant Activity Of Cat Gpx and Sodmentioning
confidence: 95%
“…3 Malignant cells have been the revelation to have the abnormal standard of antioxidant enzymes and efficacy when contrasted with normal cells. 4 However, antioxidant enzyme performance also differs between different tumors. 5 Antioxidant enzymes used to be found in different isoforms, intracellularly and extracellularly, and their action inspires an integrated antioxidant defense system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of antioxidant system is particularly important in lung carcinomas as lung tissue is highly susceptible to oxidative stress-induced damage [ 11 ]. One recent study has demonstrated that the activities of different SOD isotypes and catalase are low in lung cancer cells than adjacent normal cells; however, the activities of GPX, glutathione reductase, and glutathione S-transferase are higher in lung cancer cells [ 12 ].…”
Section: Introductionmentioning
confidence: 99%